2018
DOI: 10.1002/hep.29540
|View full text |Cite
|
Sign up to set email alerts
|

C/EBP homologous protein–induced loss of intestinal epithelial stemness contributes to bile duct ligation–induced cholestatic liver injury in mice

Abstract: Activation of ER stress and subsequent loss of stemness of ISCs plays a critical role in BDL-induced systemic inflammation and cholestatic liver injury. Modulation of the ER stress response represents a potential therapeutic strategy for cholestatic liver diseases as well as other inflammatory diseases. (Hepatology 2018;67:1441-1457).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 48 publications
4
45
1
Order By: Relevance
“…A previous study demonstrated that CHOP deficiency reduced bile duct ligation-induced disruption of tight junctions. This study reported no changes in mRNA and protein levels of tight junctions but did observe a mislocation of tight junction proteins such as occludin [297].…”
Section: Discussioncontrasting
confidence: 52%
“…A previous study demonstrated that CHOP deficiency reduced bile duct ligation-induced disruption of tight junctions. This study reported no changes in mRNA and protein levels of tight junctions but did observe a mislocation of tight junction proteins such as occludin [297].…”
Section: Discussioncontrasting
confidence: 52%
“…However, a recent study that used bile-duct ligation in mice as a model of cholestatic liver injury demonstrated that gut leakiness was associated with increased intestinal endoplasmic reticulum stress, intestinal epithelial cell apoptosis, and reduced expression of epithelial stem cell marker LGR5. 135 Nakamoto et al 127 demonstrated enrichment of Klebsiella pneumoniae in fecal samples from patients with PSC who also had ulcerative colitis. Colonization of mice with patient-derived fecal microbes showed that specific strains of K pneumoniae invaded the intestinal mucosa and increased gut leakiness, and were also found to induce pore formation in epithelial monolayer in vitro.…”
Section: Primary Sclerosing Cholangitismentioning
confidence: 99%
“…In contrast, the overexpression of transcription factor Chop exacerbated DSS-induced colitis, which seems due to impaired epithelial cell proliferation rather than increased apoptosis [ 27 ]. Consistently, a recent study showed that the absence of CHOP alleviates bile duct ligation-induced loss of stemness in intestinal stem cells, although the underlying mechanism is unclear [ 28 ]. Besides ER stress, eIF2 α phosphorylation serves as the regulatory hub of the so-called integrated stress response, which can also be initiated by three other serine/threonine eIF2 α kinases in response to distinct stimuli including viral infection (via the double-stranded RNA-activated protein kinase, a.k.a.…”
Section: Cellular Stress Signaling In Gastrointestinal Tractmentioning
confidence: 70%